1997
DOI: 10.1002/(sici)1097-4547(19970615)48:6<524::aid-jnr5>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Functional recovery from sciatic nerve crush lesion in the rat correlates with individual differences in responses to chronic intermittent stress

Abstract: The aim of the present study was to monitor the influence of chronic stress on functional recovery from a sciatic nerve crush lesion in the rat. Male Wistar rats underwent standard unilateral sciatic nerve crush. Subsequently, chronic stress was induced during the recovery phase using a daily 30 min shock box session where rats received three electric footshocks each session (0.5 sec, 1 mA). Reduced body weight gain, adrenal gland hypertrophy, and thymus involution indicated that the stress rats were chronical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Differential regeneration into the peripheral targets of the L4 and L5 DRGs has been reported (Puigdellivol-Sanchez et al, 2005), while full sensory and motor recovery after SNA has been described in as little as three weeks in rats (Vogelaar et al, 2004). Stress appears to affect several parameters of recovery (van Meeteren et al, 1997), and the process is clearly responsive to sex-specific steroids (Roglio et al, 2008) and age (Kang and Lichtman, 2013).…”
Section: Experimental Methods Of Nerve Injury and Their Consequencesmentioning
confidence: 99%
“…Differential regeneration into the peripheral targets of the L4 and L5 DRGs has been reported (Puigdellivol-Sanchez et al, 2005), while full sensory and motor recovery after SNA has been described in as little as three weeks in rats (Vogelaar et al, 2004). Stress appears to affect several parameters of recovery (van Meeteren et al, 1997), and the process is clearly responsive to sex-specific steroids (Roglio et al, 2008) and age (Kang and Lichtman, 2013).…”
Section: Experimental Methods Of Nerve Injury and Their Consequencesmentioning
confidence: 99%
“…Chronic stress deteriorates the efficiency of these processes; for example, activation of the autonomic nervous system causes epineural vasoconstriction and reduces endoneural nerve blood flow. 24 Likewise, Amako et al found suppressed sciatic nerve recovery after water-immersion stress in rats. 25 …”
Section: Discussionmentioning
confidence: 98%
“…However, it is possible that WA treatment produced occult stress that offset potentially beneficial effects of the treatment, explaining why whisking recovery that was similar to, or worse than, that of the restrained control rats, as has been demonstrated in prior studies; Van Meeteren et al demonstrated that chronic intermittent stress impaired nerve regeneration in a sciatic nerve model. 24 The nerve regeneration process is controlled by neuroendocrine, immunologic and autonomic nervous system factors. Chronic stress deteriorates the efficiency of these processes; for example, activation of the autonomic nervous system causes epineural vasoconstriction and reduces endoneural nerve blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…However, conflicting results on peripheral nerve regeneration have been reported; some studies have reported that both the forced exercises may cause detrimental effects, especially on the restoration of muscle function [3, 4]. Stress induced by forced physical training could be a factor that may impede functional recovery after nerve injury [5]. …”
Section: Introductionmentioning
confidence: 99%